Lakehouse: a framework for socially responsible strategy - Spicer, Andre (Henry Stewart Talks, 2018)
This case study charts the rise of Lakehouse, a company focused primarily on building affordable housing for public sector organisations. After some success, Lakehouse’s founder launched Building Lives: Training Academy. This academy not only provided local people with skills and employment but allowed Lakehouse to develop a skilled workforce and gain preference from the local authorities that awarded public sector contracts.